Redo inferior pubectomy for failed anastomotic urethroplasty in pelvic fracture urethral injury - Lin Wang; Wenxiong Song; Xufeng Peng; Rong Lyu; Jijian Wang; Chongrui Jin; Chao Feng; Xiangguo Lyu; Yinglong Sa; Yidong Liu (Current Urology)
Abstract. Objectives. To assess the effect of redo inferior pubectomy on the management of complicated pelvic fracture urethral injury (PFUI) in patients with a history of failed anastomotic urethroplasty. Materials and methods. We retrospectively reviewed all patients receiving redo anastomotic urethroplasty with redo inferior pubectomy for failed PFUI between January 2010 and December 2021. Patients with incomplete data and those who were lost to follow-up were excluded. Successful urethroplasty was defined as the restoration of a uniform urethral caliber without stenosis or leakage and further intervention. Functional results, including erectile function and urinary continence, were evaluated. Descriptive statistical analyses were then performed. Results. Thirty-one patients were included in this study. Among them, concomitant urethrorectal fistula occurred in 2 patients, and concomitant enlarged bladder neck occurred in 1. The stenosis site was the bulbomembranous urethra in 2 patients and the prostatomembranous urethra in 29. The mean length of urethral stenosis in all patients was 3.1 cm (range, 2.0–5.0 cm). After a mean follow-up of 34.6 months, the final success rate was 96.8%. The incidence of erectile dysfunction reached 77.4% (24/31). Normal continence was achieved in 27 (87.1%) patients. One patient developed urinary incontinence of grade II requiring urinary pads because of an enlarged bladder neck. According to the Clavien-Dindo classification, postoperative complications of grade I occurred in 7 patients and grade II in 4. Conclusions. Repeat anastomotic urethroplasty with repeat inferior pubectomy provides reliable success rates for failed PFUI. In complicated cases, it should be known and mastered.